2013
DOI: 10.3171/2013.9.jns13596
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative ischemic changes following brain metastasis resection as measured by diffusion-weighted magnetic resonance imaging

Abstract: This study demonstrates a high prevalence of vascular incidents in patients undergoing resection for metastatic brain disease. Patients harboring postoperative ischemic lesions detected by MRI have a higher rate of neurological deficits (transient or permanent). Patients who had previous irradiation therapy are at higher risk of developing postoperative ischemic lesions. A large number of postoperative neurological deficits are caused by ischemic incidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
3
16
1
1
Order By: Relevance
“…Our sample size was determined to evaluate this endpoint, which proved to be significant but too small to determine whether the association between rIPC and infarct volume is significant as well. In addition, infarct volumes were generally small in both groups, which is consistent with the results of previous studies [16, 18]. However, we found a trend toward smaller infarct volumes in the rIPC group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our sample size was determined to evaluate this endpoint, which proved to be significant but too small to determine whether the association between rIPC and infarct volume is significant as well. In addition, infarct volumes were generally small in both groups, which is consistent with the results of previous studies [16, 18]. However, we found a trend toward smaller infarct volumes in the rIPC group.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, surgical resection of brain metastases is often considered easier and less damaging to the surrounding brain tissue than the resection of glial tumors [22]. Previous studies have demonstrated differences in incidence of new postoperative ischemic lesions between these two entities [16, 17]. A retrospective study involving 122 patients with brain metastases showed that 44 patients (36.1%) had postoperative ischemic lesions, whereas another retrospective study involving glioma patients showed an incidence of 31% (26 of 84 patients) of postoperative ischemic lesions in patients with newly diagnosed gliomas and 80% (20 of 25 patients) in patients with recurrent gliomas [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Since areas around the resection cavity become ischemic after metastasis resection, 85 and residual GB cells are invariably found within 1-2 cm of an ischemic resection perimeter, these isolated pioneer cells hijack elements of the healing response, in particular G(M)-CSF increased by surgical brain tissue injury, to promote their growth in peri-resection tissue. 18 Repurposed drugs reviewed in this paper, fenofibrate, ribavirin, and dapsone, have shown ability to reduce G(M)-CSF levels or consequences of G(M)-CSF (see Table 2 for an overview).…”
Section: G(m)-csf Is a Direct Growth Factor For Gbmentioning
confidence: 99%
“…To avoid misinterpretation due to bleeding in the resection cavity, T1-weighted images without contrast agent are important for differentiation and are also routinely used in brain tumor imaging [19]. Moreover, postoperative infarction is observed after surgery of brain metastases and may cause a bias of the FLAIR signal increase [20]. However, vasogenic edema due to infarction is observed mainly in the first days after surgery and these images were excluded from analysis.…”
Section: Discussionmentioning
confidence: 99%